EXPLORING THE USE OF COLLABORATIVE STRATEGIC IN READING CLASSROOM - Mila Arizah; Lora Claudia (Universitas Putera Batam, 2020)
The study was concerned to investigate the students’ reading comprehension students of SMA Negeri 3 OKU which was taught by using Collaborative Strategic Reading. The objectives of this study was to find out the students’ reading comprehension to the eleventh grade students of SMA Negeri 3 OKU which was taught by using Collaborative Strategic Reading. The population of this study was the whole of the eleventh grade students of SMA Negeri 3 OKU. The total number of the population was 258 students; and 30 students were taken as the sample through purposive sampling. The pre-test and post-test and observation were used as the techniques for collecting the data. The researcher concluded Based on the data analysis in chapter IV, the researcher found the students’ pre test score and post-test cycle I was improved from 60,89 to 72.94. Then the students’ post-test cycle I score and post-test cycle II was improved from 72,94 to 79.74. The researcher can be concluded that Collaborative Strategic Reading worked effectively and efficiently in helping the student’s reading comprehension at the eleventh grade students of SMA Negeri 3 OKU 2018/2019 and this learning has applied successfully and able to increased students’ ability in reading comprehension. The students were more active and participated in the teaching-learning process of reading comprehension. Therefore, Collaborative Strategic Reading can be alternative strategy for teacher in teaching reading which can improve their reading comprehension ability.